From Lahore to New York: Changing Identity of Lahure in Modern Nepali Literature - Paudel, Maheswor (Bon Voyage, 2024)
This article assesses the changing identity of lahure in modern Nepali literature. Beginning with the etymology ‘lahure’ that has its one-to-one correspondence with Lahore in the then British India, this article attempts to map the expansion of that particular identity right from Nepali youths’ entrance to Lahore to serve as a mercenary for Ranjit Singh, the Khalsa warrior king and interestingly not for the British colonials, as early as 1809, that is some time before the Treaty of Sugauli in 1816 that officially opened the gate for Nepali youths to the Company Army. Deriving impetus from Craig Calhoun’s discourse of identity in reading Tulachan Ale’s Manipurko Ladai ko Sawai as the early record of the formation of the lahure identity and Sirjana Sharma’s Golden Gate as the contemporary record of such identity, this article analyzes how the identity of a lahure has significantly changed from the early Nepali youths, that too exclusively males, who visited Lahore as the pioneer migrants to British India to the Nepalis who migrate to the United States after winning lottery via the Diversity Visa Program. This article scrutinizes the loose definition of lahure in Nepali society that not only transcends the etymological meaning of the term but also deconstructs the notion of stereotypical adherence to a specific gender, that is, male.